Ethical Imperatives for Harmonizing Brain Death Standards in the United States and Globally - C. Machado; J. J. Sanchez; B. D. Saniova; M. Drobný; A. Schiff (Общая реаниматология, 2025)
The determination of brain death/death by neurological criteria (BD/DNC) is a critical medical and legal process. The Uniform Determination of Death Act (UDDA) provides a legal framework, yet significant state-by-state inconsistencies persist in its interpretation and implementation. These disparities create ethical concerns related to justice, patient autonomy, informed consent, and public trust in medical determinations of death.This paper argues for urgently harmonizing BD/DNC criteria across the United States and globally to up-hold ethical medical practice, ensure consistency in end-of-life care, and preserve public confidence in the organ donation system.Ethical considerations are examined, including fairness in healthcare access, respect for religious and cultural beliefs, and the implications for organ procurement policies. The call for national and international standardization aligns with bioethical principles and medical best practices, aiming to reinforce ethical and legal integrity in BD/DNC determination.